Myelin oligodendrocyte glycoprotein (MOG) antibody-associated encephalitis induced by Mycoplasma pneumoniae infections - Yan-Ru Liu; Xiang-Dong Zeng; Ying Xiong (BMC, 2024)
Abstract Background This study aims to report the phenomenon of Myelin oligodendrocyte glycoprotein antibody-associated encephalitis induced by Mycoplasma pneumoniae infections and promote the potential benefits of combining early immunotherapy and anti-M-pneumoniae therapy for these patients. Methods Three children with MOG-IgG-associated encephalitis due to M. pneumoniae infections who were treated at our hospital from September to November 2023 were included in the study. We investigated and analyzed the background and clinical features of these patients. Results Three patients developed headaches, seizures, and/or other neurological manifestations, elevated mononuclear cells in cerebrospinal fluid, intracranial lesions on cranial magnetic resonance imaging (MRI), and positive MOG-IgG in serum, within 10-14 days. They were diagnosed with MOG-IgG-associated encephalitis due to M. pneumoniae infections, the treatment consisted of intravenous immunoglobulin, glucocorticoid, and erythromycin, then they were completely recovered. Conclusion Mycoplasma pneumoniae (M. pneumoniae) infections can cause oligodendrocyte glycoprotein (MOG) antibody-associated encephalitis. The recognition of this condition will promote the potential benefits of combining early immunotherapy and anti-M. pneumoniae therapy for patients with MOG-IgG-associated encephalitis.